Bank Size and Lending Specialisation. (15th May 2017) - Bonfim, Diana; Dai, Qinglei
Abstract : Using micro‐level data on the entire population of business loans of a bank‐based economy, we empirically test some of the core predictions of the small and medium enterprise (SME) financing literature, examining banks' lending specialisations in firm size and lending technologies. Rejecting the conventional belief that smaller banks focus more on relationship loans than larger banks, we find that relationship lending is equally common for small and large banks. However, supporting the SME finance theories on the organizational advantages of small banks, we find that smaller banks provide more access to relationship loans to small firms, though such loans are usually more expensive.